THE PLACE OF ADMINISTRATIVE LAW NORMS IN THE SYSTEM OF LEGAL PRINCIPLES OF PREVENTIVE ACTIVITIES OF INTERNAL SECURITY UNITS (Bulletin of criminological association of Ukraine, 2024)
It is concluded that the legal principles of preventive activities of internal security units of the National Police of Ukraine should be characterized as a set of fundamental provisions established by regulatory legal acts of various legal force, which contain its main directions, forms and methods of implementation, objects of influence, as well as the purpose of implementation. It is noted that today the system of relevant principles is quite limited. Basically, the relevant regulatory legal acts: 1) regulate the direct functioning of internal security units, outline the scope of counteraction to offenses that impede the effective work of the National Police of Ukraine; 2) determine the directions of implementation of relevant preventive measures implemented within the framework of such counteraction; 3) establish the obligations of employees of the National Police of Ukraine to protect human rights and freedoms, which they implement as representatives of a law enforcement agency, and the violation of which is the object of preventive measures of internal security units. It is noted that today it is necessary to adopt a unified regulatory legal act on the prevention of offenses, which should define the objects and subjects of such activities, their functions, general and individual preventive measures, their consequences, legal protection of the person in respect of whom prevention of offenses is carried out, etc. It is summarized that among the legal principles of the studied sphere of preventive activity, administrative and legal norms occupy a decisive place. They establish the powers of employees of the internal security units of the NPU to carry out measures related to the prevention of offenses, including in relation to certain areas of internal security support (record keeping, access regime to the premises of the NPU, use of certain means of operational and investigative activity, anti-corruption activity).
Keywords: legal principles; regulatory legal acts; preventive activity; internal security units